Physical geology of the Fogo volcano (Cape Verde Islands) and its 2014–2015 eruption. (31st July 2015) - Worsley, Peter
Abstract : The geological development of the Fogo island volcano commenced in the early Quaternary, and much later during the Last Glacial stage this involved a mega‐scale lateral collapse of the former edifice. This later event created a large caldera‐like landform open to the east, the floor of which is known as the Chã, and subsequently within this a strato‐volcanic cone has grown. The last phase of volcanic activity started in late 2014 and persisted for 77 days. It had a devastating impact on the lives of the 1000 plus people who were living within the 'caldera', since two large villages and a smaller one were each totally destroyed in a matter of days by the advancing lavas. In addition, large areas of cultivated land, upon which the inhabitants were dependent for their livelihood, were enveloped by lava. The eruption proved to be of a greater magnitude than the immediately preceding one of 1995, when a mass evacuation was necessary but as only a few buildings were affected, resettlement followed. Unfortunately the much greater devastation to the human environment makes it doubtful whether any significant resettlement will be possible after the 2014–2015 event.